Discipline and Debate the Language of Violence in a Tibetan Buddhist Monastery. - Lempert, Michael (Berkeley : University of California Press, 2012)
The Dalai Lama has represented Buddhism as a religion of non-violence, compassion, and world peace, but this does not reflect how monks learn their vocation. This book shows how monasteries use harsh methods to make monks of men, and how this tradition is changing as modernist reformers--like the Dalai Lama--adopt liberal and democratic ideals, such as natural rights and individual autonomy. In the first in-depth account of disciplinary practices at a Tibetan monastery in India, Michael Lempert looks closely at everyday education rites--from debate to reprimand and corporal punishment. His analys.
Cover; Title; Copyright; Contents; List of Illustrations; Acknowledgments; Technical Note on Transcription and Research Methods; Introduction: Liberal Sympathies; Part One: Debate; 1. Dissensus by Design; 2. Debate as a Rite of Institution; 3. Debate as a Diasporic Pedagogy; Part Two: Discipline; 4. Public Reprimand Is Serious Theatre; 5. Affected Signs, Sincere Subjects; Conclusion: The Liberal Subject, in Pieces; Notes; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y.
Description based on print version record.
Keywords: Buddhist monasticism and religious orders -- Education -- China -- Tibet Autonomous Region; Liberalism (Religion) -- India; Violence -- Religious aspects -- Buddhism; Discipline -- Religious aspects -- Buddhism; Tibetans -- India -- Religion; RELIGION / Buddhism / General; Electronic books